2011
DOI: 10.1038/jid.2010.429
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy–Induced Immunosuppression in Humans Is Prevented by Reducing the Rate of Light Delivery

Abstract: Photodynamic therapy (PDT) of non-melanoma skin cancers currently carries failure rates of 10-40%. The optimal irradiation protocol is as yet unclear. Previous studies showed profound immunosuppression after PDT, which may compromise immune-mediated clearance of these antigenic tumors. Slower irradiation prevents immunosuppression in mice, and may be at least as effective as high-fluence-rate PDT in preliminary clinical trials. The photosensitizers 5-aminolaevulinic acid and/or methyl aminolaevulinate were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
3
26
0
1
Order By: Relevance
“…41,42 PDT was shown to trigger immune suppression at high irradiances but immune stimulation at low irradiances in normal skin. 22 This is interesting from the perspective of different death modes observed at high and low irradiance in our study. Stimulation of antitumor immunity after PDT is recognized, but the details/trigger mechanisms are still discussed.…”
Section: Apoptosis Inductionmentioning
confidence: 76%
See 1 more Smart Citation
“…41,42 PDT was shown to trigger immune suppression at high irradiances but immune stimulation at low irradiances in normal skin. 22 This is interesting from the perspective of different death modes observed at high and low irradiance in our study. Stimulation of antitumor immunity after PDT is recognized, but the details/trigger mechanisms are still discussed.…”
Section: Apoptosis Inductionmentioning
confidence: 76%
“…Thus, high irradiance was found to be immunosuppressive, whereas a similar total dose administered using lower irradiance was not immunosuppressive. 22 In the present study, we have used five different human cancer cell lines and compared the overall PDT efficiency when using HAL-induced PpIX as photosensitizer activated by light of either 410 or 624 nm. We observed substantial differences among the cell types in their sensitivities to light.…”
mentioning
confidence: 99%
“…This is opposite to the effects of radio-and chemotherapy and surgery which are immunosuppressive [91]. However, recent reports on non melanoma skin cancer ALA treatment have indicated that PDT induced immunosuppression can occur and can be prevented by using lower light doses [92].…”
Section: Vascular Effects In Pdt Generalmentioning
confidence: 56%
“…Light delivery at lower fluence rate can inhibit PDT-induced inflammation, under the condition that the full dose of an effective treatment regimen is delivered at the low rate [9]. Interestingly, low fluence rate can also abrogate PDT-induced immunosuppression [22]. In a rodent peritoneal model of ovarian cancer, Estevez et al [23] showed that even a small decrease in fluence rate from 30 to 20 mW/cm 2 for hexaminolaevulinatemediated PDT of equal treatment length led to increases in the frequency of fullthickness necrosis of tumor nodules.…”
Section: Fluence Rate Effectsmentioning
confidence: 96%